Associations between salivary testosterone levels, androgen-related genetic polymorphisms, and self-estimated ejaculation latency time - Patrick Jern; Lars Westberg; Carina Ankarberg-Lindgren; Ada Johansson; Annika Gunst; Kenneth Sandnabba; Pekka Santtila (John Wiley & Sons Ltd., 2022)
<div id="sm234-sec-0001" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Introduction
Recently, testosterone (T) has been shown to be associated with premature ejaculation (PE) symptoms in the literature. Furthermore, studies suggest that the etiology of PE is partly under genetic control.
<div id="sm234-sec-0002" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Aim
The aim of this study was to reassess findings suggesting an association between testosterone (T) and a key symptom of PE, ejaculation latency time (ELT), as well as exploratively investigating associations between six androgen-related genetic polymorphisms and ELT.
<div id="sm234-sec-0003" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Materials and Methods
Statistical analyses were performed on a population-based sample of 1,429 Finnish men aged 18–45 years (M = 26.9, SD = 4.7). Genotype information was available for 1,345–1,429 of these (depending on the polymorphism), and salivary T samples were available from 384 men. Two androgen receptor gene-linked, two 5-alpha-reductase type 2-gene-linked, and two sex hormone-binding globuline gene-linked polymorphisms were genotyped.
<div id="sm234-sec-0004" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Main Outcome Measures
Ejaculatory function was assessed using self-reported ELT.
<div id="sm234-sec-0005" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Results
We found no association between salivary T levels and ELT. We found a nominally significant association between a 5-alpha-reductase type 2-gene-linked polymorphism (rs2208532) and ELT, but this association did not remain significant after correction for multiple testing. One single nucleotide polymorphism in the sex hormone-binding globulin gene (rs1799941) moderated (significantly after correction for multiple testing) the association between salivary T and ELT, so that A:A genotype carriers had significantly lower salivary T levels as a function of increasing ELT compared with other genotype groups.
<div id="sm234-sec-0006" style="margin: 0px; padding: 0px; border: 0px; outline: 0px; font-size: 10px; vertical-align: baseline; overflow: hidden; font-family: Arial, 'Lucida Grande', Geneva, Verdana, Helvetica, 'Lucida Sans Unicode', sans-serif; line-height: 10px; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">
Conclusions
We were unable to find support for the hypothesis suggesting an association between T levels and ELT, possibly because of the low number of phenotypically extreme cases (the sample used in the present study was population based). Our results concerning genetic associations should be interpreted with caution until replication studies have been conducted.